Study on the Development of Water Crisis in Bali Island in 2009 and 2013 - Sunarta, I Nyoman; Rahman, Abd.; syakur, As- (E-Journal of Tourism; Volume 2 Number 1 (March 2015), 2015)
Water resources are one of the most important natural resources for human life in carrying out their various activities. Bali is a relatively a small island as well as a center for the development of tourism in Indonesia. The population as well as the number of tourists keeps increasing every year which has resulted in the water crisis problem. The development of the water crisis derived from the ratio of the amount of water supply to the amount of water demand in the Island of Bali. Water supply is determined by using the runoff coefficient method which was modified from the rational method. By co-relating the runoff coefficient with the average rainfall and the size of the island, the supply of water can be determined. The water demand is determined by using the variable of the population size and the Falkenmark indicator. The development of the water crisis is determined by comparing the amount of supply and demand of water in 2009 and 2013. The result of the calculation showed that the total water supply in Bali in 2009 amounted to 4.71 billion m3 / year and decreased to 3.57 billion m3 / year in 2013. During that period, the total water demand increased; in 2009 it amounted to 5.46 billion m3 / year and in 2013 it amounted to 6.23 billion m3 / year. Thus, Bali has experienced a water deficit in 2009 and in 2013. The condition of Bali in 2009 showed that out of the 9 districts / cities, five experienced a water deficit, whereas in 2013 it increased to 8 districts / cities that have experienced a water deficit. Therefore, Bali should take serious steps to save water resources, not only to save the tourism development, which has become the mainstay of Bali, but also for the sustainability of the Balinese people’s lives.
Keywords: water resources, water crisis, Bali island